FACTORS AFFECTING THE USE OF DIGITAL PAYMENTS IN INDONESIA EVIDENCE FROM GLOBAL FINDEX DATABASE 2021 - Yuan Swastika; Sofian Maksar, Muhammad; Cahyani, Eka Angelina (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Digital payment is a type of payment that uses electronic means such as Internet Banking. Digital payments have become an integral part of modern life, driven by technological developments, changes in consumer behavior, and the need for efficiency.. This study aims to determine the influence of demographic factors (gender, age, education, and area of residence) and economic factors (occupation, income, and internet access) on the use of digital payments in Indonesia. Based on the results of data processing using StataMp17 (64 bit), the results of the study show that demographic factors of gender, education, and area of residence have a significant influence on the use of digital payments, but demographic factors of age show results that do not have a significant effect on the use of digital payments. While economic factors of work and internet access have a significant influence on the use of digital payments, but economic factors of income show results that do not have a significant effect on the use of digital payments.